The Effectiveness of Wood Vinegar and Ecoenzyme as Organic Biostimulants on the Growth of Tomato Plants (Solanum lycopersicum L.) - Agri Anugrah; Arif Budiman; Zakiyah Amini (Ann Publisher, 2026)
Background. Wood vinegar is a by-product of the pyrolysis of biomass such as wood. Wood vinegar is also known as liquid smoke/pyroligneous acid. Wood vinegar is formed from the incomplete combustion of lignocellulosic materials. Wood vinegar produces compounds that have antimicrobial, antibacterial, and antioxidant effects. Aims. This study aimed to determine the effect of wood vinegar and ecoenzyme application on the vegetative growth of Servo tomato (Solanum lycopersicum L.) plants. Methods. The study used a Randomized Block Design (RBD) with 9 treatment combinations of wood vinegar (0, 10, and 15 mL/L water) and ecoenzyme (0, 10, and 15 mL/L water) and 3 replicates. The parameters observed included plant height and number of leaves at 10, 17, 27, 37, and 47 days after planting (DAP). The data were analyzed using Analysis of Variance (ANOVA) and followed by Duncan's Multiple Range Test (DMRT) at a 5% level. Result. The results showed that the application of a combination of wood vinegar and ecoenzyme had a very significant effect on the vegetative growth of tomato plants at all observation ages (p < 0.05). The best treatment was P8 (15 mL/L wood vinegar + 15 mL/L ecoenzyme), with the highest average number of leaves (114.67) and plant height (66.83 cm) at 47 DAP. The combination of these two materials worked synergistically to increase nutrient availability, enhance soil microbial activity, and stimulate the production of natural growth hormones (auxin and cytokinin). Conclusion. Meanwhile, the medium concentration at P6 (10 mL/L wood vinegar + 15 mL/L ecoenzyme) also showed a significant increase in leaf number and plant height compared to the control. Implementation. The use of a combination of wood vinegar and an ecoenzyme has been proven to optimally enhance the vegetative growth of Servo tomato plants. It can serve as a potential environmentally friendly organic biostimulant to replace chemical fertilizers.